ANALISIS HARGA POKOK PENJUALAN DALAM RANGKA MENINGKATKAN LABA PADA UD. TAHU CITRA DOLOKSANGGUL - Silalahi, Rianda; Sembiring, Sabeth (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study aims to analyze the cost of goods in order to increase profits at UD. Tahu Citra Doloksanggul. The population in this study is sales, the cost of production which includes: raw material costs, direct labor costs, factory overhead costs, cost of goods sold, operating expenses and company profits since the establishment of UD. Tahu Citra Doloksanggul 2003-2022. The research sample is sales, the cost of production which includes: raw material costs, labor costs, factory overhead costs, cost of goods sold, operating expenses and company profits in 2020-2021. The data collection technique used is the documentation technique. The data analysis technique used is descriptive. Based on the results of research and discussion, it is concluded that the calculation of the cost of goods sold in 2020 is Rp. 1.023.740,000 and in 2021 it is Rp. 1.076.240.000. In 2021 it will increase due to an increase in raw material prices. The purchase price of raw materials in 2020 is Rp. 10.500 per kg, increasing in 2021 to Rp. 11.200. This can affect the calculation of the cost of goods sold and also on UD. Tahu Citra profit. Know Image. Efforts to increase profits at UD. Tahu Citra by minimizing costs related to the cost of goods sold amounting to Rp. 1.021.340.000. Where the elements of cost of goods sold are minimized, namely: raw material costs Rp. 831.600.000, labor costs Rp. 120.000.000, and factory overhead costs Rp. 69.740.000. With the decrease in the cost of goods sold, UD. Tahu Citra will be able to increase profits by Rp. 192.640.000 Keywords: Cost of Goods Sold, Increase Profit